Toward carbon free energy. - Sweet, W. (IEEE spectrum)
In this paper the authors describe how heavy reliance on coal in huge countries like China and India threatens the whole world's climate. They state how they believe that the utmost ingenuity will be needed to minimize adverse effects of that dependence